Guidelines for the prevention and management of children and adolescents with COVID-19 - Liu, Enmei; Smyth, Rosalind Louise; Li, Qinyuan; Qaseem, Amir; Florez, Ivan D.; Mathew, Joseph L.; Amer, Yasser Sami; Estill, Janne; Lu, Quan; Fu, Zhou; Lu, Xiaoxia; Chan, Edwin Shih‑Yen; et al. (Springer Science and Business Media Deutschland GmbH, 2022)
Children are the future of the world, but their health and future are facing great uncertainty because of the coronavirus disease 2019 (COVID-19) pandemic. In order to improve the management of children with COVID-19, an international, multidisciplinary panel of experts developed a rapid advice guideline at the beginning of the outbreak of COVID-19 in 2020. After publishing the first version of the rapid advice guideline, the panel has updated the guideline by including additional stakeholders in the panel and a comprehensive search of the latest evidence. All recommendations were supported by systematic reviews and graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Expert judgment was used to develop good practice statements supplementary to the graded evidence-based recommendations. The updated guideline comprises nine recommendations and one good practice statement. It focuses on the key recommendations pertinent to the following issues: identification of prognostic factors for death or pediatric intensive care unit admission; the use of remdesivir, systemic glucocorticoids and antipyretics, intravenous immunoglobulin (IVIG) for multisystem inflammatory syndrome in children, and high-flow oxygen by nasal cannula or non-invasive ventilation for acute hypoxemic respiratory failure; breastfeeding; vaccination; and the management of pediatric mental health. Conclusion: This updated evidence-based guideline intends to provide clinicians, pediatricians, patients and other stakeholders with evidence-based recommendations for the prevention and management of COVID-19 in children and adolescents. Larger studies with longer follow-up to determine the effectiveness and safety of systemic glucocorticoids, IVIG, noninvasive ventilation, and the vaccines for COVID-19 in children and adolescents are encouraged.What is Known:• Several clinical practice guidelines for children with COVID-19 have been developed, but only few of them have been recently updated.• We developed an evidence-based guideline at the beginning of the COVID-19 outbreak and have now updated it based on the results of a comprehensive search of the latest evidence.What is New:• The updated guideline provides key recommendations pertinent to the following issues: identification of prognostic factors for death or pediatric intensive care unit admission; the use of remdesivir, systemic glucocorticoids and antipyretics, intravenous immunoglobulin for multisystem inflammatory syndrome in children, and high-flow oxygen by nasal cannula or non-invasive ventilation for acute hypoxemic respiratory failure; breastfeeding; vaccination; and the management of pediatric mental health.